PREGNANT TEENS PROFILE OF USERS OF HEALTH FAMILY UNIT IN LOWLAND CROSS - SOUSA-PB. (Fiep Bulletin - online, 2011)
Adolescence is a period characterized by the transition from childhood to adult, so it is a period of deep instability emotional and bodily changes. The objective is to analyze the profile of pregnant teenagers users of prenatal ESF Lowland Cross, Sousa-PB. It is a study of quantitative and qualitative nature, whose population consisted of pregnant adolescent women users of this unit and the sample consisted of adolescent women who become pregnant. Data were collected in April and May 2008.It was used as an instrument of data collection a questionnaire with 18 questions objective guiding the profile of these adolescents in reproductive stage. It is observed that 77.6% of interviewed who were between 17 to 20 years. In the case of marital status 66.7% were single. 77.8% had incompleted primary school. 44.4% had incomes below the minimum wage amount of people living at home ranged from 55.5% at 4 to 6 people. About their experience in the current pregnancy was possible to divide them into two central ideas: satisfaction and dissatisfaction. Through this it is clear that, although teenage pregnancy has been identified as a public health problem, it is not always fact inconsistent and disastrous.
Keywords: USF; Teenager; Pregnancy